АКТИВНІ ТЕХНОЛОГІЇ ПІДГОТОВКИ ДИТИНИ до школи (Педагогіка вищої та середньої школи, 2010)
In article the authors analyzes the outstanding teachers position as for the necessity of the childrens preparation to school and the technology of this preparation.